Criticism and Correction on Suboptimal Javanese-Indonesian Code-Switching in “KKN di Desa Penari” and “Sewu Dino” - Ibnuz Zaki (Journal of English Language Teaching and Linguistics, 2025)
As something created with an emphasis on intentionality, art, in this case film, should pose some levels of reasoning behind what is shown in it. This is especially true when what is shown is a representation of a specific real-life culture with its own intricacies, rules and values. This study is based on such notion regarding the act of language representation in film, specifically on some seemingly lacking in intentions or functions in executing Javanese-Indonesian language dynamic in a form of code-switching practice that to me could see some improvements to make it more appropriate while at the same time more aesthetically pleasing. With considerations such as social status, age, education and place of living, this study discusses some suboptimal Javanese-Indonesian code-switching representation in two successful Indonesian horror films “KKN di Desa Penari” and “Sewu Dino”. The discussion involves patterns and language tendencies found in the two films’ characters’ use of Javanese-Indonesian code-switching, lack of clear purpose, intention and function behind said patterns and tendencies, and finally subsequent corrections or improvements that could have been taken in such cases of code-switching contexts.